Letters from Heaven, Love Mom Xo - Sandy Bucholz
"Letters From Heaven, Love Mom xo" by Sandy Bucholtz is a series of inspiring letters written from a mother to her children, so they will always experience her love and gain from her wisdom, even in the time of her absence. Be a part of this magnificent work of heartfelt passion. Add your own personal pictures and words of wisdom to the available pages of this book for the ones you love, knowing that no matter where you are, you will always be with them.